Corporate social responsibility and data privacy in multinational enterprises : Is corporate social responsibility a guarantee for data privacy? - Schröder, Ida (My University, 2022)
A study on corporate social responsibility, multinational enterprises, and data privacy based on literature utilizing the legal dogmatic research method, post-positivism, and internal critique. Corporate social responsibility has become more and more relevant for multinational enterprises. At the same time, the importance and need for data privacy are growing quickly. Multinational enterprises have found a way to include data privacy in their corporate social responsibility policies due to different reasons. Multinational enterprises have the ability to spread data privacy standards through corporate social responsibility policies. Corporate social responsibility policies on data privacy tend to have the same content, which further helps with spreading data privacy standards. The ones that are guaranteed data privacy are individual users of the multinational enterprise, others have to trust the multinational enterprise’s ability to spread and maintain data privacy standards. The effect of spreading and maintaining standards is the same no matter the level of regulation on data privacy.

Tämä pro gradu -tutkielma on kirjallisuuteen perustuva tutkimus yritysten yhteiskuntavastuusta, monikansallisista yrityksistä ja tietosuojasta. Tutkielmassa on hyödynnetty oikeusdogmaattista tutkimusmenetelmää, postpositivistista tutkimusmenetelmää ja sisäisen kritiikin tutkimusmenetelmää. Yritysten yhteiskuntavastuu on tullut yhä tärkeämmäksi monikansallisille yrityksille. Samaan aikaan tietosuojan merkitys ja tarve on kasvanut nopeasti. Monikansalliset yritykset ovat ajan myötä alkaneet sisällyttämään tietosuojakäytäntöjä vastuullisuusraportteihinsa eri syistä. Monikansallisilla yrityksillä on mahdollisuus levittää tietosuojakäytäntöjään yritysten yhteiskuntavastuun avulla. Monikansallisten yritysten vastuullisuusraporteissa on yleensä samankaltainen sisältö, ja tämä koskee myös tietosuojakäytäntöjä. Vastuullisuusraporttien sisältö pohjautuu ihmisoikeuksiin ja lainsäädäntöön. Tietosuojakäytäntöjen levittäminen ja yhtenäistäminen on helpompaa, kun vastuullisuusraporttien sisältö on samankaltainen. Tietosuoja on taattu monikansallisten yritysten yksittäisille käyttäjille, mutta muiden täytyy luottaa monikansallisten yritysten kykyyn levittää ja ylläpitää tietosuojakäytäntöjä. Tietosuojakäytäntöjen levittämisen ja ylläpitämisen vaikutus on sama tietosuojan sääntelyn tasosta riippumatta.
Keywords: CSR, corporate social responsibility, data privacy, corporations, international law, yhteiskuntavastuu, tietosuoja, monikansalliset yritykset, kansainvälinen oikeus